Determination of Resistance to Creep Permanent Deformation of Hot Mix Asphalts Prepared with Various Additives - Erkut Yalçın; Muhammed Ertuğrul Çeloğlu; Mehmet Yılmaz; Baha Vural Kök; Taner Alataş (Salehan Institute of Higher Education, 2018)
In this study, the resistance of hot mix asphalts containing different additives to the creep permanent deformation was investigated by the dynamic creep test. Four different additives were used in the study. Styrene-butadiene-styrene (SBS), American Gilsonite (AG), and Iranian Gilsonite (IG) were used for modifying the bitumen. Additionally, the same mixtures were prepared by using 2% hydrated lime as filler. The samples were subjected to dynamic creep test at 50°C under 500 kPa stress level. As a result of the tests performed, it has been determined that all of the additives used in the study improve the resistance to the creep permanent deformation. It has also been determined that the use of bitumen additives is more effective than the use of lime. Furthermore, it has been determined that the most effective additive is IG while the least effective additive is SBS, and hydrated lime use is more effective compared to the mixtures prepared with a neat binder.